Karonda: A nutritionally rich crop suitable for arid ecosystem - Meena, Nirmal Kumar; M, Menaka; R, Vinod B; Choudhary, Kalpana (Indian Horticulture, 2023)
Climate change has emerged as critical global problem, hampering productivity and production of perennial horticultural crops. Under the biotic and abiotic stresses, there is a need to explore some hardy indigenous crops which can sustain by mitigating these adverse conditions. Among them, Karonda is an emerging underutilized fruit, gaining economic importance due to its enormous health and wealth benefits. It is a very rich source of phytonutrients, especially iron and ascorbic acid. In addition to that, fruits are used for preparing many processed products like jam, jelly, RTS, squash and pickle. Karonda pickle is very famous in some central parts of India and now-a-days, Karonda jam is getting high commercial value. To improve its varietal wealth, some elite genotypes from its diversity centre need to be collected and evaluated. Collection, evaluation and conservation of elite genotypes for the crop improvement is being done in different parts of the country. Under the scenario of climate change, hardy crops like Karonda could replace the major cultivated fruit crops and be cultivated commercially for sustainable development.